The effects of crocin on psychological parameters in patients under methadone maintenance treatment: a randomized clinical trial - Anahita Khalatbari-mohseni; Hamid Reza Banafshe; Naghmeh Mirhosseini; Zatollah Asemi; Amir Ghaderi; Abdollah Omidi (BMC, 2019)
Abstract Background Methadone maintenance treatment (MMT) might be associated with the symptoms of depression and anxiety, sleep disturbances and sexual dysfunctions. This study was designed to determine the effects of crocin on psychological parameters in patients under MMT. Methods Patients under MMT were randomly allocated into two groups to receive either 30 mg/day crocin (2 plus crocin tablet, 15 mg BID) (n = 25) or placebo (2 tablets per day, 15 mg BID) (n = 25), one hour after taking food, for 8 weeks. Psychological parameters were evaluated at baseline and end of the trial to determine related associations between crocin and patients' mental health status. Results After 8-week intervention, crocin significantly decreased Beck Depression Inventory (b − 6.66; 95% CI, − 9.88, − 3.45; P < 0.0001), Beck Anxiety Inventory (b − 4.35; 95% CI, − 5.94, − 2.75; P < 0.0001), general health questionnaire (b − 4.45; 95% CI, − 7.68, − 1.22; P = 0.008) and Pittsburgh Sleep Quality Index (b − 2.73; 95% CI, − 3.74, − 1.73; P < 0.0001) in patients under MMT, compared with the placebo. Crocin also significantly improved International Index of Erectile Functions (b 4.98; 95% CI, 2.08, 7.88; P = 0.001) rather than placebo. Conclusion Our findings indicated that taking crocin for 8 weeks by patients under MMT had beneficial effects on their mental health status. Crocin can be recommended as an adjunct to methadone in opioid withdrawal protocols because of the ability to improve the quality of life and decrease opioids side effects in these patients. This trial was registered in the Iranian website for clinical trials registry as http://www.irct.ir: IRCT2017110537243N1. Clinical trial registration number www.irct.ir: http://www.irct.ir: IRCT2017110537243N1.